Virulomic Analysis of Multidrug-Resistant Klebsiella pneumoniae Isolates and Experimental Virulence Model Using Danio rerio (Zebrafish) - Edson Luiz Tarsia Duarte; Camila Fonseca Rizek; Evelyn Sanchez Espinoza; Ana Paula Marchi; Saidy Vasconez Noguera; Marina Farrel Côrtes; Bianca H. Ventura Fernandes; Thais Guimarães; Claudia M. D. de Maio Carrilho; Lauro V. Perdigão Neto; Priscila A. Trindade; Silvia Figueiredo Costa (MDPI AG, 2022)
This study evaluates a possible correlation between multidrug-resistant Klebsiella pneumoniae strains and virulence markers in a Danio rerio (zebrafish) model. Whole-genome sequencing (WGS) was performed on 46 strains from three Brazilian hospitals. All of the isolates were colistin-resistant and harbored blaKPC-2. Ten different sequence types (STs) were found; 63% belonged to CC258, 22% to ST340, and 11% to ST16. The virulence factors most frequently found were type 3 fimbriae, siderophores, capsule regulators, and RND efflux-pumps. Six strains were selected for a time-kill experiment in zebrafish embryos: infection by ST16 was associated with a significantly higher mortality rate when compared to non-ST16 strains (52% vs. 29%, p = 0.002). Among the STs, the distribution of virulence factors did not differ significantly except for ST23, which harbored a greater variety of factors than other STs but was not related to a higher mortality rate in zebrafish. Although several virulence factors are described in K. pneumoniae, our study found ST16 to be the only significant predictor of a virulent phenotype in an animal model. Further research is needed to fully understand the correlation between virulence and sequence types.